Migração da erucamida em filmes de polietileno - Maziero, Kelly Cristina (2024)
Erucamide is a migrating slip additive that is added to films of polyethylene (PE) to reduce the coefficient of friction (COF). During the extrusion process, small amounts of erucamide are incorporated into the polymer matrix, which over time migrates to the surface, modifying the film's surface properties. The reduction in COF’s value depends on the actual amount of erucamide available on the surface of the film. If the migration does not occur as expected, there may be an excess or reduction of the slip additive on the film’s surface, affecting its performance. Although studies have clarified many of the characteristics of erucamide migration, maintaining COF stability for PE films under different environmental conditions and over long periods of storage has been a persistent problem for the flexible packaging industry being the COF the only analysis commonly carried out, as it is quick, easy and low-cost. In this work, a set of techniques were brought together to characterize a polyethylene film produced in 3 layers and with erucamide added to the central layer with the purpose of correlating the erucamide migration with time, temperature and the effects arising from such migration. Using DSC, TGA and High-Performance Liquid Chromatography (HPLC) techniques, the film can be characterized as low-density polyethylene (LDPE) with a concentration of approximately 3890ppm of erucamide. The degree of crystallinity affects migration, so they were evaluated using X-ray diffraction and compared with DSC technique that showed similar results. The surface distribution of the additive was observed at different times and temperatures using images collected through scanning electron microscopy (SEM). A plot of COF as a function of time, temperature and film surface morphology revealed that COF reduced quickly with increasing temperature, and after 72h the COF values for the samples stored at room temperature and for the ones stored at 50 ºC were the same, however the excess of crystals on the surface of the heated sample is clearly visible. Such excess crystals on the surface increase the film's initial sealing temperature, which is undesired in high-efficiency film processes. Therefore, any increase in sealing temperature may be related to excess erucamide on the film surface. The excess of erucamide can be detected through measuring contact angle of samples. Using FTIR-PAS, it was possible to detect erucamide in a layer very close to the surface of the film and the results corroborate the microscopy and COF analyses. Therefore, the set of techniques used in this work proved to be efficient in clarifying and finding possible solutions and corrections to any anomalies found in the film, avoiding losses and financial and environmental impacts.